Imparting aromaticity to 2-pyridone derivatives by O-alkylation resulted in new competitive and non-competitive PIM-1 kinase inhibitors with caspase-activated apoptosis - Marwa E. Abdelaziz; Mostafa M. M. El-Miligy; Salwa M. Fahmy; Marwa M. Abu-Serie; Aly A. Hazzaa; Mona A. Mahran (Taylor & Francis Group, 2024)
AbstractNew aromatic O-alkyl pyridine derivatives were designed and synthesised as Proviral Integration Moloney (PIM)-1 kinase inhibitors. 4c and 4f showed potent in vitro anticancer activity against NFS-60, HepG-2, PC-3, and Caco-2 cell lines and low toxicity against normal human lung fibroblast Wi-38 cell line. Moreover, 4c and 4f induced apoptosis in the four tested cancer cell lines with high percentage. In addition, 4c and 4f significantly induced caspase 3/7 activation in HepG-2 cell line. Furthermore, 4c and 4f showed potent PIM-1 kinase inhibitory activity with IC50 = 0.110, 0.095 µM, respectively. Kinetic studies indicated that 4c and 4f were both competitive and non-competitive inhibitors for PIM-1 kinase enzyme. In addition, in silico prediction of physiochemical properties, pharmacokinetic profile, ligand efficiency, ligand lipophilic efficiency, and induced fit docking studies were consistent with the biological and kinetic studies, and predicted that 4c and 4f could act as PIM-1 kinase competitive non-adenosine triphosphate (ATP) mimetics with drug like properties.